Mythological Narratives and Modern Reinterpretations in the Deconstruction of Narcissus Stories - -, Miranti; -, Mukodas; Balazs Huszka (Jurnal Sastra Indonesia, 2024)
A deconstructive analysis of the Narcissus story, particularly in the short story "The Black Goat of Narcissus" by Mukodas Sinatrya, offers a new perspective on how classical mythological narratives can be interpreted in a more modern and complex context. This approach allows readers to connect narrative elements with contemporary issues such as narcissism, self-identity, and the dynamics of human relationships. By conducting a comparative analysis between the original narrative and its modern reinterpretation, this article highlights the use of deconstruction techniques to dismantle and rebuild our understanding of the characteristics of Narcissus and the social and cultural implications of the story. The article explores how the Narcissus story reflects human traits and societal dynamics and serves as a medium for self-reflection and introspection. By delving into themes such as narcissism, egoism, and the complexities of self-identity, this article demonstrates that modern literary works can be essential for understanding and dealing with evolving social and cultural dynamics. Therefore, a deconstructive analysis of the Narcissus story not only yields a deeper understanding of the complexities of human nature and its social consequences but also underscores the relevance of ancient mythological narratives in helping us respond to the challenges of the modern context.